Language Transfer and Errors Transfer in Teaching A Foreign Language - Thuy, Nguyen Ngoc (Advances in Social Sciences Research Journal, 2021)
Correcting students’ language errors is always importance during teaching because of its significance for analyzing those errors and trying to provide students and teachers with adequate techniques and strategies to avoid or at least minimize the number of errors committed while practicing the foreign languages. This article will focus mainly on different ways in which an interest in language learner has revealed different aspects of the language learning process and suggested different ways of treating errors in our teaching. The objectives of the paper are mainly to understand the origins of an interest in errors that learners made and the related development of the concept of interlanguage , to appreciate the significance of learner error and how it might affect our methodology and to realize some of the causes of errors including positive and negative transfer. Furthermore, the article will explain the concept of systematic variability in learner language in order to become aware of some of the causes and significances of variability.